Anthropogenic Changes in the Frequency and Severity of European Winter Storms - Pardowitz, Tobias (2015)
Abstract iii Zusammenfassung v 1 Introduction 1 1.1 Objectives of the Thesis . . . . . . . . . . . . . . . . . . . . . . . . . . . . 5 1.2 Outline of the Thesis . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 5 2 Projected Changes in European Winter Storm Climate 9 2.1 Introduction and Current State of Research . . . . . . . . . . . . . . . . . 9 2.2 Data and Methods . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 11 2.2.1 Reanalysis Data . . . . . . . . . . . . . . . . . . . . . . . . . . . . 11 2.2.2 Global Climate Model Output . . . . . . . . . . . . . . . . . . . . 11 2.2.3 Wind Field Tracking . . . . . . . . . . . . . . . . . . . . . . . . . . 12 2.2.4 Storm Severity Index . . . . . . . . . . . . . . . . . . . . . . . . . . 13 2.2.5 Extreme Value Analysis . . . . . . . . . . . . . . . . . . . . . . . . 15 2.3 Recent and Future Winter Storm Frequency . . . . . . . . . . . . . . . . . 20 2.3.1 Statistical Uncertainty and Natural Variability . . . . . . . . . . . 24 2.3.2 Scenario Uncertainty . . . . . . . . . . . . . . . . . . . . . . . . . . 25 2.3.3 Model Uncertainty . . . . . . . . . . . . . . . . . . . . . . . . . . . 27 2.4 Intensities of Recent and Future Winter Storms . . . . . . . . . . . . . . . 30 2.4.1 Statistical Uncertainty . . . . . . . . . . . . . . . . . . . . . . . . . 35 2.4.2 Scenario Uncertainty . . . . . . . . . . . . . . . . . . . . . . . . . . 36 2.4.3 Model Uncertainty . . . . . . . . . . . . . . . . . . . . . . . . . . . 37 2.5 Summary and Discussion . . . . . . . . . . . . . . . . . . . . . . . . . . . 41 3 Mechanisms Related to Changes in European Winter Storm Climate 45 3.1 Introduction and Current State of Research . . . . . . . . . . . . . . . . . 45 3.2 Data and Methods . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 47 3.2.1 Reanalysis Data . . . . . . . . . . . . . . . . . . . . . . . . . . . . 47 3.2.2 Global Climate Model Data . . . . . . . . . . . . . . . . . . . . . . 47 3.2.3 Assessment of the North Atlantic Oscillation . . . . . . ...